2020
DOI: 10.1186/s13054-020-03348-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anticoagulation strategies for veno-venous ECMO support in acute respiratory failure

Abstract: Background Extracorporeal membrane oxygenation (ECMO) support in acute respiratory failure may be lifesaving, but bleeding and thromboembolic complications are common. The optimal anticoagulation strategy balancing these factors remains to be determined. This retrospective study compared two institutional anticoagulation management strategies focussing on oxygenator changes and both bleeding and thromboembolic events. Methods We conducted a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…The same results were presented in a systematic review [ 158 ]. However, in an even more recent retrospective analysis, it was found that “ECMO management with high-dose heparinization was associated with lower rates of oxygenator changes and thromboembolic events when compared to a low-dose heparinization strategy” [ 159 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…The same results were presented in a systematic review [ 158 ]. However, in an even more recent retrospective analysis, it was found that “ECMO management with high-dose heparinization was associated with lower rates of oxygenator changes and thromboembolic events when compared to a low-dose heparinization strategy” [ 159 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…Although the PMEA-coated system we employed is indicated to reduce circuit-related adverse effects such as inflammatory responses and thrombo-coagulopathies, these findings were obtained only by either in vitro studies or short-term uses. In addition, only a few case-based studies reported feasibility of long-term VV-ECMO with low-dose anticoagulant uses [ 9 , 10 ]. Therefore, we needed to pay considerable attention to coagulation status in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our group demonstrated that different heparin monitoring and dosing strategies result in ample differences in BTE occurrence with mean heparin doses differing by 60% between experienced centers and, quite unsurprisingly, bleeding occurring far more often with higher heparin doses, while thrombotic events peak with lower doses [2].…”
mentioning
confidence: 90%
“…Author details 1 Hannover Medical School, Department of Respiratory Medicine and Biomedical Research in End-Stage and Obstructive Lung Disease Hannover, German Center for Lung Research, Hannover, Germany. 2 Institute of Intensive Care Medicine, University Hospital Zurich, Zurich, Switzerland. 3 Department of Gastroenterology, Hepatology and Endocrinology, Hannover Medical School, Hannover, Germany.…”
Section: Declarationsmentioning
confidence: 99%